Studi Kelayakan Operasi Berdasarkan Uji Dissolve Gas Analysis pada Transformator Distribusi 150 kV Gardu Induk Cibabat Cimahi - Handoko Rusiana Iskandar (KILAT, 2021)
The role of insulation media in high voltage equipment is an important component in maintaining the ongoing distribution of electric power from random interference during operation. Insulation media used in high voltage equipment are air, solid, oil, or gas. All of these media will experience a decrease in performance along with the operating time and service life factor of the equipment. Therefore, the role of maintenance is very important. One method of diagnosis of damage to insulating oil is Dissolve Gas Analysis (DGA). DGA diagnosis is conducted to determine the rate of gas growth in the insulating oil in parts per million (ppm). Some DGA methods are Total Dissolve Combustible Gas (TDCG), Duval’s Triangle, and Roger’s Ratio. A sampling of transformer oil isolation in this study was conducted on three transformer units in the 150 kV / 20 kV Cibabat Cimahi Substation. Oil samples are tested through data processing based on IEEE Std C57.104-2008 standards and SPLN T5.004-5: 2017. DGA test results in the laboratory of PT. PLN (Persero) UPT Bandung shows the results of TDCG transformer unit 1 in condition 2 with the amount of flammable gas at 821 ppm, for transformer unit 2 in condition 1 with the amount of combustible gas 694 ppm and transformer unit 3 in condition 2 with combustible gas 1117 ppm so that each gas growth rate for transformer unit 1 is -1.36 ppm/day, transformer unit 2 is -1.03 ppm/day and transformer unit is 3 0.95 ppm/day.